Gene expression profiles in the spinal cord following transected injury. Issue 1 (28th March 2017) - Liu, Jia; Hu, Yue; Hu, Yuan‐Dong; Xia, Qing‐Jie
Abstract : Objective: Spinal cord transection (SCT), one of the common spinal cord injuries (SCI), could induce motor and behavioral deficits. With the deep understanding of SCI, there are certain progresses in the field of basic and clinical research, but these results are far from satisfaction due to the complex mechanism. Particularly, the gene expression have shown an important role the development of SCI. Thus modifying the gene expression may be a potential therapeutical target for SCI. This study is designed to investigate the gene map in transected spinal cord. Methods: SCT model was established by the spinal cord transection at the segment of T10. Modified Basso, Beattie, and Bresnahan (BBB) scores were used to evaluate the motor function of rats. Then, microarray analysis was performed to screen the gene expression profile after 14 days. The intensity ratio > 2 or < 0.05 were regarded as differentially expressed genes. Genes ontology analysis including BP, CC and MF, were used to analyze the function and pathway of these genes. Results: After SCT, the BBB scores were significantly lower than that of the sham group. Microarray analysis showed that there were 3059 upregulate genes and 3320 downregulated genes in spinal cord of SCT group. Analysis of these genes showed that cellular response to stimulus, staphylococcus aureus infection, glutamatergic synapse etc, participated in the SCI process. Conclusion: These findings showed SCT regulated multiple gene expression, which might be associated with the multiple pathological changes. These further indicated that the occurrence of SCI was not a single gene or a single factor, but a complex pathophysiological process.